Characteristics of the effect of exosomes isolated from donor plasma and placenta-derived mesenchymal stromal cell-conditioned medium on the paracrine secretion of human peripheral blood mononuclear cells - L. V. Natrus; Yu. H. Klys; D. O. Labudzynskyi; P. A. Chernovol; R. N. Khairnasov; P. F. Muzychenko; I. M. Ryzhko (Zaporožskij Medicinskij Žurnal)
Extracellular small vesicles – exosomes, attract the attention of researchers as a promising tool for regulating intercellular communication. At the same time, the therapeutic effects achieved through the use of mesenchymal stem cells (MSCs) are traditionally considered by medicine as a time-tested, multi-vector strategy for the treatment of various pathologies. In particular, in addition to the application of MSCs directly, it is important to study the products of their secretion.